Synergistic effects of platelet-rich fibrin and CTLA4Ig gene-transfected porcine skin on accelerating wound healing in a rat model of deep second-degree burns: a mechanistic study - Li, Jiliang; Xu, Chongwei; Chen, Leyi; Lou, Jiaqi; Kong, Hong; Fan, Youfen (Frontiers in Immunology, 2026)
BackgroundDeep second-degree burns impair skin regeneration and carry high risks of scarring and infection. Achieving healing with minimal immune rejection remains challenging. Platelet-rich fibrin (PRF), an autologous biomaterial, promotes angiogenesis and repair via sustained growth factor release. CTLA4Ig, an immunomodulatory agent, can suppress T-cell-mediated rejection. We hypothesized that combining PRF with CTLA4Ig gene-transfected porcine skin would synergistically enhance wound healing by concurrently stimulating regeneration and modulating local immunity.MethodsA standardized deep second-degree burn was created on the dorsum of 32 Sprague-Dawley rats, randomly divided into four groups (n=8): Vaseline group, PRF group, Pigskin group, and PRF+pigskin group. Wound closure was tracked macroscopically for 21 days. Histological analysis (H&E, Masson’s trichrome), immunohistochemistry for CD31, VEGF, the pro-inflammatory cytokines IL-6 and TNF-α, and immunofluorescence staining for the antioxidant enzymes catalase (CAT) and superoxide dismutase 1 (SOD1) were performed on days 4, 7, 14, and 21.ResultsThe combination treatment (PRF+pigskin group) demonstrated a significant acceleration in wound closure compared to all other groups, with near-complete re-epithelialization observed by day 14. Statistical analysis confirmed a significant interaction between Treatment and Time (p<0.001), suggesting a synergistic healing pattern. Histological examination revealed more organized and dense collagen fibers, with the most pronounced effect in PRF+pigskin group. Immunohistochemical and immunofluorescence analyses indicated a marked upregulation of CD31-positive vessels, VEGF expression, and antioxidant enzymes (CAT and SOD1) in the combination group, indicating a trend towards enhanced angiogenesis and an augmented capacity to mitigate oxidative stress. Concurrently, immunohistochemistry for IL-6 and TNF-α revealed a significant attenuation of these pro-inflammatory cytokines in the PRF+pigskin group and the pigskin group, particularly at the later stages of healing (D14, D21), indicating a modulation of the local inflammatory response.ConclusionThe concomitant application of PRF and CTLA4Ig gene-transfected porcine skin suggests a synergistic effect, creating a pro-regenerative, immunomodulatory, anti-inflammatory, and antioxidative microenvironment. This resulted in significantly accelerated and improved healing of deep second-degree burn wounds, representing a promising and innovative therapeutic paradigm for the management of severe burns.